Evaluation of coeffecient of consolidation and compression index of Kuantan clayey soils stabilised by recycled and reused soils stabilised by recycled and reused materials mixed with portland cement - Peng Yang, Chua (2013)
This thesis presents the evaluation for the coefficient of consolidation and compression index of Kuantan soils using variable reused and recycled materials mixed with Portland cement. The objective of this thesis is to evaluate the change of compression index, void ratio, and coefficient of consolidation of Kuantan Clayey stabilized by recycle and' reuse material mixed with Portland cement by using one-dimensional consolidation test and study the engineering properties of clay soil before and after undergoing one-dimensional consolidation test. This thesis describes the onedimensional consolidation tests done to compute the changes of compressibility and justify the suitable amount of additives used. Crushed glass, shredded carpet fibres, fly ash, and shredded high density polyethylene plastic which are classified as recyle and reused materials were added into Kuantan clay soil and then mixed with Portland cement to study and evaluate the Kuantan clay in term of compressibility. In this thesis, the values of coefficient of consolidation and compression index soils were done using a One-dimensional consolidation test. The analysis of the test was performed semiautomatically using One-dimensional consolidation program from ELE International. After analysis by the system, the coefficient of consolidation and compression index of the samples obtained were employed as parameter to find the compressibility of Kuantan clay soil. From the results conducted, analysis of using fly ash blend is more conservative reading in coefficient of consolidation indicated better rate of consolidation. Still, soil sample added with crushed glass mixed with Portland cement performed better decrement in compression index indicated better performance in compressibility. The achieved results utilizing high density polyethylene and carpet fibres gave low performance in compressibility compared to crushed glass and fly ash. In conclusion, after comparing all the recycled and reused materials, crushed glass mixed with Portland cement is the most capable treatments to improve engineering properties of Kuantan clay. The results can also considerably reduce the cost of construction and materials to improve soils stability in Kuantan, Pahang.